Spatial distribution of butterfly (lepidoptera: papilionoidea) along altitudinal gradients at Gunung Ledang National Park, Johor, Malaysia - Ismail, Norradihah; Mohamed, Maryati; Phon, Chooi Khim; Tokiman, Lili (2018)
Gunung Ledang, or previously known as Mount Ophir is the highest highland in south Peninsular Malaysia, in the state of Johor. Along with its elevations, climate, and vegetation vary. These influence the distribution of flora and fauna such as butterfly. The objectives of this study were (i) to document the diversity of butterfly along elevational gradients and (ii) to analyze species diversity patterns based on faunistic aspect. To determine spatial distribution, this study was conducted at three different altitudes; 1 200 m, 800 m, and 400 m above sea level (a.s.l.). Samplings were conducted from May 2014 until Feb 2015. During the eight sampling occasions, two main methods were employed; manual collection using the aerial net and baited trapping using rotten fruits. A total of 635 individuals comprising 129 butterfly species from five families were recorded. The five families were Papilionidae, Pieridae, Nymphalidae, Lycaenidae, and Hesperiidae. Nymphalidae was the most well-represented family by 58.1 % species richness and 80.3 % abundance. At all elevations, eight species were consistently found. They were: Eurema hecabe, Euploea mulciber, Ideopsis gaura, Mycalesis maianeas, Ypthima pandocus, Cirrochroa malaya, Cirrochroa orissa, and Hypolimnas bolina. There were highly significant differences (p < 0.001) in the diversity of butterfly species between elevations. The values of Shannon Diversity Index (H’) was highest, 4.179 at 400m and lowest, 1.792 at 1 200 m. Meanwhile, the Species Evenness Index (E’) at 400 m was 0.660 and at 1 200 m was 0.162. These indicated that lowest altitude (400 m) would harbor higher species diversity and more even species distribution compared to the two higher altitudes. Spatially, the diversity of butterfly in a highland forest of Malaysia was established, providing a baseline data that would be useful for monitoring and conservation of a protected area such as Gunung Ledang National Park.